Efficacy and safety of first-line chemotherapy combined with immune checkpoint inhibitors for extensive-stage small cell lung cancer patients: a real-world propensity score matching study - Jia, Bin; Zhou, Chenyi; Zhao, Fei; Song, Xiaoru; Ding, Yuan; Wang, Xiyin; Wu, Boying; Wang, Huina; Hu, Quanman; Chen, Shuaiyin (Frontiers in Immunology, 2025)
Backgroundextensive-stage small cell lung cancer (ES-SCLC) were the majority of SCLC patients. Recently the combination of chemotherapy with immune checkpoint inhibitors (ICIs) have emerged as the new first-line treatment standard for ES-SCLC. However, the specific patient populations that are most likely to benefit from this treatment remains to be clearly identified making the establishment of baseline biomarkers critical.MethodsWe recruited ES-SCLC patients who were treated at the First Affiliated Hospital of Zhengzhou University and conducted a propensity score-matched analysis (PSM). And used the Kaplan-Meier (K-M) method and Cox proportional hazards regression to compare the survival outcomes. In addition, univariate and multivariate COX regression analyses were conducted to identify predictors.ResultsAfter-PSM, chemotherapy group had a longer median overall survival (mOS) of 15.23 months (95%CI: 14.00-17.87) and hazard ratio (HR) of 0.576 (95% confidence interval (CI): 0.404-0.821), P=0.002), and the median progression free survival (mPFS) in the chemotherapy group was shorter: 6.05months (95%CI: 4.33-7.87), HR=0.707 (95%CI: 0.526 -0.950, P=0.021) compared to before PSM. Multivariate analysis confirmed that Eastern Cooperative Oncology Group performance status (ECOG PS) =1 (HR: 2.36, 95% CI: 1.38-4.03, P=0.002) and brain metastases (HR: 2.08, 95% CI: 1.05-4.14, P=0.038) were independent prognostic factors for PFS, and only systemic inflammation response index (SIRI)> 2.63 (HR: 0.06, 95% CI: 0.01-0.29, P<0.001) was an independent prognostic factor for OS.Conclusionour findings indicate that incorporating ICIs into first-line chemotherapy significantly improves PFS and OS in ES-SCLC patients, while maintaining safety. Moreover, poor ECOG PS, brain metastases, and high SIRI at baseline may serve as valuable prognostic indicators for disease progression and survival in ES-SCLC patients undergoing first-line chemotherapy plus ICIs. It is worth noting that these findings should be interpreted as hypothesis-generating, not definitive clinical conclusions.